Condition factor, heavy metals and polychlorinated biphenyls (PCBs) in the muscle of fishes harvested in, and imported into Lagos, Nigeria - Oyelowo Oluwakemi; Awobajo Funmileyi; Samuel Titilola; Sogbesan Teniola; Fayiga Adewale; Mofolorunso Adekunle (Aceh Journal of Animal Science, 2020)
Fish is an important part of the human diet, are at the top of the aquatic food chain with a high propensity to accumulating contaminants like heavy metals and polychlorinated biphenyls (PCBs) which are toxic to humans.  The objective of this study was to evaluate the relationship between condition factor (physiologic wellbeing) of the fishes, PCBs, and heavy metal accumulation.Ten adult fish species three each of Chrysichthys nigrodigitatus, Trachinotus teraia, Liza dumerilli, Tilapia guieensis, Pseudotolithus elongatus, Pomadasys jubelini, Polydactylus quadrifilis, Caranx hippos, Sphyreana barracuda, Arius heudoloti,were acquired at Epe Lagoon. Ten adult fish species three each of Argentina silus, Gadus chalcogrammus, Gadus morhua, Atlantic mackerel, Micropogonias undulatus, Urophycis sp., Chrysichthys nigrodigitatus, Oreochromis niloticus, Clupea harengus, Trachurus trachurus, imported into Lagos were purchased. The fish species’ condition factor was determined. The heavy metals were determined using AAS while PCB level was determined using GC-MS. Iron, mercury, zinc, arsenic, nickel and copper levels correlated positively with the condition factor in the local fishes while in the imported fishes, cadmium, iron, zinc, nickel, copper and lead levels correlated positively to the condition factor. The levels of PCBs in both the local and imported fishes were non-detectable.  It is concluded that the lead, copper, arsenic, zinc, mercury and cadmium in both the imported and local fishes were within permissible limits compared with the FAO/WHO maximum permissible limits. The positive correlation of some heavy metals to the fishes’ condition factor infers that these metals might be altering physiologic activities in the fishes. Keywords: Condition factor; Heavy metals; Polychlorinated biphenyl; Fish